Effect of organic manures, PGPR and micronutrients on yield and quality enhancement in ajwain (Trachyspermum ammi L): Yield and quality enhancement in ajwain through organic substitutes and micronutrients - Thanuja, G S; Srinivasulu, B; Yuvaraj, K M; Giridhar, K. (Journal of Spices and Aromatic Crops, 2021)
Experiments were conducted for two consecutive years during 2017-19 to study the effect of organic manures, PGPR and micronutrients on yield and quality of ajwain seed. Farm yard manure (FYM) and vermicompost (VC) were used as organic sources at 50% and 75% recommended dose of nitrogen (RDN) as basal dose. PGPRs namely Azospirillum lipoferum, Bacillus megaterium and Frateuria aurantia were used for seed priming. Micronutrients namely ZnSO4 and Fe2SO4 were applied thrice as foliar application @ 0.5% first before flowering, second at 50% flowering and third during grain formation. The results revealed that highest number of umbels plant-1, umbellets umbel-1, number of fruits umbellet-1, seed yield plant-1, seed yield hectare-1, straw yield, biological yield, test weight of seeds and essential oil yield were recorded with the application of 50% RDN through VC, which was on par with 50% RDN through FYM, seed priming with Azospirillum and foliar application of zinc with respect to their individual effect. Maximum essential oil content, fixed oil content and thymol content were also observed in case of application of 50% RDN through VC, seed priming with Azospirillum and foliar application of zinc individually. Highest Benefit Cost Ratio (BCR) of 3.33 was recorded with combined application of 50% of RDN through FYM along with seed priming with Azospirillum and foliar spray of Zn at 0.5%. The integrated use of organic manures, PGPRs and micronutrients could also exert significant influence on yield and quality of Ajwain. It was observed that highest seed yield, yield attributing characters and essential oil yield and quality parameters were recorded with combined application of 50% of RDN through vermicompost along with seed priming with Azospirillum and foliar application of zinc which was statistically on par with application of 50% of RDN through FYM along with seed priming with Azospirillum and foliar application of zinc.